PHYSICO-CHEMICAL BASIS OF THE EFFECT OF AROMATIC AMINO COMPOUNDS ON MAINTAINING PLANT MOISTURE (International journal of artificial intelligence, 2025)
This article analyzes the role of aromatic amino compounds in maintaining plant moisture and their physicochemical properties. Research results indicate that aromatic amino compounds play a crucial role in plant water exchange processes. The mechanisms of moisture retention in plant tissues and the involvement of aromatic amino compounds in these processes are examined in detail.